Kinerja Keuangan Sebelum Dan Saat Pandemic Covid-19 Pada Perusahaan Telekomunikasi Yang Tercatat Di Bursa Efek Indonesia - Ananda Widiastuti; Jaeni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
The purpose of this study was to determine differences in the financial performance of telecommunication companies listed on the Indonesia Stock Exchange before and during the COVID-19 pandemic. The method in this research uses descriptive quantitative. The sampling technique was carried out by purposive sampling. The type of data used is secondary data obtained from the Indonesia Stock Exchange in the form of financial reports for the first quarter - fourth quarter of the Telecommunication Sector Company for the period 2018 and 2020. The research variables used are Current Ratio, Net Profit Margin, Return On Assets, Debt to Asset Ratio and Debt to Equity Ratio. The results of this study indicate a significant difference in the Current Ratio and Debt to Asset Ratio While the Net Profit Margin, Return On Assets and Debt to Equity Ratio there are no significant differences